Estimation of Physical Activity Level in Elderly Nursing Home Residents - Tanaka, Kiyoshi; Ohta, Junko; Fujii, Ayano; Kuwabara, Akiko (Eiyōgaku zasshi, 2013)
Objective: According to the 2010 edition of Dietary Reference Intakes for Japanese (DRIs-J), the estimated energy requirement (EER) is calculated as the basal metabolic rate (BMR) multiplied by the physical activity level (PAL). Nutritional management is expected to be performed on an individual basis for the elderly nursing home residents, and therefore, knowledge regarding the appropriate EER is essential. These subjects are highly problematic in that they have extremely large differences in their BMR and PAL. In this study, we preliminarily analyzed the methods for PAL estimation in these subjects. Subjects and Methods: The study subjects were 28 elderly women who had been nursing home residents for more than three months, and the inclusion criteria were body weight changes of less than 3% and serum albumin level higher than 3.6 g/dl. BMR was estimated using two equations: first, the one by the National Institute of Health and Nutrition (NIHN), and second, the one in the 2010 edition of DRIs-J. The estimated PAL was defined as the total energy intake divided by the BMR. Results: There were no differences in terms of age, height, weight, BMI, or serum albumin levels between the subjects receiving nursing care levels 1-2 and those receiving nursing care levels 3-5. The estimated PAL was lower in the former than in the latter, although these findings were not statistically significant. PAL estimated on the basis of the NIHN equation exceeded 1.8 in 10 of the subjects, which was considered inappropriately high. Conclusions: PAL estimated by various equations have given different results. Further studies are warranted regarding the determination of PAL in nursing home residents.